A systematic review of progress toward unlocking the power of epigenetics in breast cancer: latest updates and perspectives - Alotaibi, Ghallab (Frontiers in Pharmacology, 2025)
Breast cancer (BC) is among the most prevalent malignancies globally. It is progressively acknowledged as a diverse type of cancer, exhibiting considerable differences in its genomic and transcriptomic characteristics. Its growing evidence highlights the substantial role of epigenetic modification in pathogenesis, prognosis and treatment. Cancer and epigenetics are closely linked; abnormal epigenetic changes can influence numerous aspects of cancer biology, including unusual transcription patterns, initiation of cancer, its progression, resistance to drugs, and metastasis. Epigenetic drugs (epi-drugs), including DNA methyltransferase (DNMT) and histone deacetylase (HDAC) inhibitors, serve as promising therapeutic agents, particularly in combination with conventional therapies. Additionally, nanotechnology-assisted epi-drug delivery systems are emerging as innovative approaches to enhance treatment efficacy and reduce systemic toxicity. While several epigenetic biomarkers have shown potential in liquid and tissue biopsies, their clinical validation remains a challenge. The integration of epigenetic insights into personalized medicine could revolutionize BC management, offering more targeted and effective treatment strategies. This systematic review aims to evaluate recent advancement in epigenetic research related to BC, focusing on diagnostic and prognostic biomarkers, epigenetic-based therapies and ongoing clinical trials. A comprehensive literature search was carried out in databases like PubMed, Scopus, and Google Scholar up to January 2025, following PRISMA guidelines. Seventy two (72) studies were included, addressing key aspects of DNA methylation, histone modification, and non-coding RNAs as potential biomarkers for early detection and disease progression monitoring.